The Buchanan-Wagner Hypothesis: Revisiting the Theory with New Empirics for a Spendthrift Democracy - Konukcu Onal, Debi (Panoeconomicus, 2024)
This study revisits the Buchanan-Wagner hypothesis in reference to the deficit-spending dynamics of Turkey in the period 1924 to 2008, during which the government was expanding along with the developing national economy and democracy. The empirical analysis of the hypothesis is based on the autoregressive distributed lag approach to cointegration, which is not only quite new in the literature on the Buchanan-Wagner hypothesis but also superior to other single-equation cointegration approaches. The prevailing empirics for the Buchanan-Wagner hypothesis reveal deficiencies in several respects, as they ignore the mixed orders of integration in regressors, the endogeneity of regressors, and the encompassing dynamic structure in the short and long runs. Within this context, the findings of this study imply the validity of the hypothesis for Turkey, providing empirical evidence on the premise that budget deficits financed by nontax sources are the main driving force behind the continuously increasing public spending in Turkey. This evidence is argued to be a reflection of the fact that the perceived tax price of public goods and services decreases with debt-financed budget deficits over time. Keywords: Buchanan-Wagner hypothesis, Budget deficits, Public spending, Turkey, Autoregressive Distributed Lag (ARDL) approach JEL: C50, H41, H60